Honduras' Energy Policy: Post Coup d'état Energy Scenarios. (25th November 2018) - Flores, Wilfredo C.
Abstract : Since the 2009 coup d'état, Honduras' energy sector has experienced radical changes. The Honduran electricity market was liberalized, and electricity distribution was granted. The installation of photovoltaic projects in the country's electricity grid was stimulated via incentives and increased investment in renewable energy projects. Additionally, the Energy Secretary was recently created by decree, but the sector still suffers from scattered, biased legislation, and institutional weakness. An important new issue related mainly to the high investment in renewables in isolated areas is the social effect, leading to social unrest, because many of the areas where these projects are being carried out are inhabited by indigenous communities. Moreover, the effects of climate change have not been included in studies on the nation's energy policy. This article analyzes the most‐relevant factors that should be included in an update of Honduras' energy policy, considering a post‐coup reality. The Long Energy Alternatives Planning software is used to model energy scenarios.